Satellite orbit and attitude simulator: design and implementation - Okasha, Mohamed Elsayed Aly Abd Elaziz; Mohammad Abdelrahman, Mohammad Ibraheem (2013)
In this paper, a graphical user interface (GUI) simulator is developed to analyze the satellite orbital and attitude motion during each mode of operation. This tool enables the mission analysis engineer to quickly assess the satellite performance and to verify the mission analysis requirements. In addition, it can be used to test the performance of the satellite attitude control algorithms during the entire satellite mission. Numerical examples showing the analysis and performance using this tool is presented for a low Earth orbit satellite.